Clinical features and treatment outcomes for primary cutaneous CD4+ small/medium T-cell lymphoproliferative disorder: a retrospective cohort study from the Dana-Farber Cancer Institute and updated literature review. Issue 12 (15th October 2022) - Plumptre, Isabella R.; Said, Jordan T.; Sun, Tiffany; Larocca, Cecilia; Virgen, Cesar A.; Kupper, Thomas S.; Fisher, David C.; Devlin, Philip M.; Elco, Christopher P.; Song, Johanna Sheu; LeBoeuf, Nicole R.
Abstract: Primary cutaneous CD4+ small/medium T-cell lymphoproliferative disorder (PCSM-TCLPD) was reclassified in 2016 as a rare benign entity with an excellent prognosis, yet its clinical features and best treatments remain poorly defined. We collected clinical data, treatments, and treatment-responses from our institution's patients with PCSM-TCLPD through September 2018 and an identical PubMed review through June 2021. Among 36 cases (median-age 54 years; 58.3% head/neck), diagnostic biopsy resulted in sustained complete remission (CR) in 13/33 punch/shave biopsies and 3/3 excisional biopsies. The remaining 20 patients further required topical corticosteroids ( n  = 5); intralesional corticosteroids ( n  = 1); surgical-excision ( n  = 5); electron-beam-radiation ( n  = 6); or brachytherapy ( n  = 3). All patients ultimately achieved CR, excluding one patient continuing treatment at end-of-study. 57/59 (96.6%) of institutional and literature-reported radiation-treated patients experienced CR. No institutional cases progressed beyond skin; 5/209 (2.4%) literature-reported cases progressed to systemic/extracutaneous involvement, all pre-reclassification. PCSM-TCLPD responds well to local-directed therapy including radiation, and only rarely if ever progresses.